Pengaruh model pembelajaran kooperatif tipe numbered head together berbantuan quizizz terhadap kemampuan berpikir kritis pada pembelajaran ips kelas v sd - Adisya Kharisma Haqqi; Jenny Indrastoeti Siti Poerwanti (Didaktika Dwija Indria, 2025)
The problem in this study is that students were not yet accustomed to thinking critically and have not been optimal in using learning models and media. This study aims to determine the effect of the NHT type cooperative learning model assisted by Quizizz on critical thinking ability in IPS learning for fifth-grade students in elementary school. The type of research used is quasi-eksperimental method and the research design used is pretest-posttest control group design. The population and sample of the study were all fifth-grade Gugus III Gajah Mada, Banjarsari district with the sample used amounted to 172 students. The sampling technique used in this study was cluster random sampling technique. Data analysis techniques using independent sample t test. The result of the independent test calculation show less than 0,05 (Sig.) so it can be concluded that there is an effect of the NHT type cooperative learning model assisted by Quizizz on critical thinking ability skills in IPS learning for fifth-grade students of elementary school Gugus III Gajah Mada Banjarsari district.